Conception rate of Filial Friesian Holstein cows after being inseminated using unsexed and sexed semen - Firdaus, Amir; Utami, Putri; Ramadhani, Anisa; Asshidiq Syah, Habib; ShikhMaidin, Mashitah; Anugra Yekti, Aulia Puspita; Nurul Isnaini; Trinil Susilawati (Universitas Brawijaya, 2024)
This research aimed to increase the reproduction of dairy cows with artificial insemination (AI) in Filial Friesian Holstein cows using sexed semen. This research was conducted in Pandesari Village, Pujon District, Malang Regency, East Java. The 114 Filial Friesian Holstein cows were used in this research and divided into three Treatments: T1: 38 cows were inseminated using unsexed semen, T2: 38 cows were inseminated using albumin sedimentation sexed semen, and T3: 38 cows were inseminated using Percoll density gradient centrifugation (PDGC) sexed semen. The material was selected by purposive sampling with a minimum body condition score (BCS) specification of 2.5 (scale 1-5); the material had normal reproductive organs and showed signs of heat/estrus. The parameters of this study are the percentage of non-return rate (NRR) 1, NRR 2, and conception rate (CR). The data obtained were analyzed using descriptive analysis. The differences in NRR and CR between the unsexed sperm, sexed sperm with albumin sedimentation, and sexed sperm with PDGC were analyzed with the chi-square test and were considered significant at p < 0.05. The chi-square test was carried out to compare the observed values with the expected values. The results showed that the success of artificial insemination was greater by using albumin-sedimented sexed semen compared to unsexed semen or PDGC-sexed semen, with NRR values of 1 (95%), NRR values of 2 (87%) and CR values of 63%. The conception rate of artificial insemination using albumin-sedimented sexed semen was 63% greater than that of artificial insemination using unsexed semen and PDGC-sexed semen, which obtained the same value of 47%.